ChemInform Abstract: Stereoselective Organocatalytic Addition of Nucleophiles to Isoquinolinium and 3, 4‐Dihydroisoquinolinium Ions: A Simple Approach for the Synthesis of Isoquinoline Alkaloids. Issue 13 (March 2015) - Gualandi, Andrea; Mengozzi, Luca; Manoni, Elisabetta; Cozzi, Pier Giorgio
Abstract Review: 118 refs.